2016
DOI: 10.4236/cs.2016.78180
|View full text |Cite
|
Sign up to set email alerts
|

Malicious Nodes Detection in MANET Using Back-Off Clustering Approach

Abstract: Mobile Ad hoc Networks (MANET) are infrastructure less networks which provide multi-hop wireless links between nodes. The main applications of MANET in real time environment are military and emergency areas where the fixed infrastructure is not required. It is a temporary communication infrastructure network for quick communication with minimal configuration settings among the group of nodes. The security is one of the primary concerns in MANET. The malicious nodes in MANET environment degrade the performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…From Figure 1, it can be observed that the performance of the system which is proposed by Rajeswari et al (2016) is better when it is compared with other existing systems. Which system used soft computing techniques such as neural network, genetic algorithm and fuzzy logic achieved better accuracy than other systems.…”
Section: Results Analysismentioning
confidence: 95%
See 2 more Smart Citations
“…From Figure 1, it can be observed that the performance of the system which is proposed by Rajeswari et al (2016) is better when it is compared with other existing systems. Which system used soft computing techniques such as neural network, genetic algorithm and fuzzy logic achieved better accuracy than other systems.…”
Section: Results Analysismentioning
confidence: 95%
“…Ganapathy et al (2016) proposed a new IDS with the combination of the Intelligent CRF-based feature selection and the layered approach for effective intrusion detection. Rajeswari et al (2016) proposed a new IDS for detecting malicious nodes in MANETs using backoff clustering method. The advantage of their system is to identify, detect and prevent the novel attacks effectively.…”
Section: Work On Ids For Manetmentioning
confidence: 99%
See 1 more Smart Citation